Inoculation of substrate with lactic acid bacteria for the development of Moringa oleifera Lam plantlets - Anguiano Soto, J. M.; Anguiano Cárdenas, J.; Palma García, J. M. (Cuban Journal of Agricultural Science, 2017)
The objective of this study was to evaluate the inoculation of substrate with lactic acid bacteria in the development of Moringa oleifera Lam plantlets. For the production of lactic acid bacteria (LAB) three treatments with ferments of ripe tropical fruits were established: Musa spp. (banana LABB), Cucurbita pepo L. (pumpkin LABP) and Carica papaya L. (papaya LABP) and a control treatment. The application of these treatments was carried out in three moments of the Moringa oleifera development: to the sowing, with the first true leaves and ten days after this stage. The obtained results showed emergence percentages of 67, 61 and 61 % vs 34 % for LABP, LABP, LABB vs control, also at plant height (P < 0.001) and fresh weight (P < 0.001) and dry weight (P < 0.001).The higher values were obtained for the treatments with ALBP with respect to the control. However, the root length was higher in LABP and LABB with respect to the rest of treatments (P < 0.001). In the number of leaves, a positive effect was obtained initially, favoring the use of LAB with respect to the control (P < 0.001), with no statistical effect on insertion of the first branch (P > 0.05). It is concluded that the use of inoculum of lactic bacteria from the fermentation with pumpkin, banana and papaya resulted in an ecotechnology that promotes the emergence and development of Moringa oleifera plantlets. Key words: forage, growth, nursery, LAB, trees